PEMBERIAN PUPUK MAJEMUK NPK DAN Cu UNTUK PERTUMBUHAN TANAMAN KELAPA SAWIT BELUM MENGHASILKAN (Elaeis guineensis Jacq.) DI LAHAN GAMBUT - M Ade Syahputra; Wardati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Fertilization is a factor that must be considered to improve the growth of oil palm plant on peatland. Applications of sufficient and balanced fertilizer is needed to support the growth of oil palm. One way to get a good growth of oil palmon peatland is by providing essential nutrients both macro and micro. This research aims to determine the interaction of NPK and Cu compound fertilizeras well as finding the best dose for growth of immature oil palm plants. This research arranged experimentallyby using randomized block design (RBD), consistof 16 combinations that repeated 3 times, so obtained 48 units experiment, that 1 unit consists of 2 plants. The observed parameterswere the plant height increase, stem girth increase, number of midrib increase andlength of midrib increase. The results showed that the interaction of NPK and Cu compound fertilizerat dose of 800 g/plant NPK and 75 g/plant Cu fertilizer gave the best effect on the length of midrib increase. Keywords: NPK compoundfertilizer, peatland